Harry Potter and the Chamber of Secrets - Book 2 - Rowling, J.K. (New York : Arthur A. Levine Books, 1999)
When the Chamber of Secrets is opened again at the Hogwarts School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Keywords: Potter, Harry (Fictitious character) -- Fiction; Wizards -- Great Britain; Fiction; Magic -- Great Britain; Fiction; Schools -- Great Britain; Fiction; Great Britain -- Fiction; Fantasy